Navigating Challenges in Islamic Education: Strategic Management for Community Involvement and Modernization - Pitri, Alisyah; Yamin, Martinis; Halim, Abdul (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the strategic management of SMPIT (Integrated Islamic Junior High School) An Nahl Percikan Iman Jambi in building relationships with the community, using the Nine-Step Strategic Planning theory and Gitney’s Hierarchy of Needs. This qualitative research employs a phenomenological approach, with data collection techniques including interviews, observations, and documentation. The findings indicate that SMPIT An Nahl Percikan Iman implements a series of well-planned and directed strategic management efforts to strengthen relationships with the community, including: (1) fostering connections through social service activities, (2) collaborating with educational institutions, and (3) actively engaging parents in school activities. A key strength of the communication efforts at SMPIT An Nahl Percikan Iman lies in the involvement of middle-class parents, who actively support the school’s programs. The school’s public relations initiatives are also supported by: (1) the utilization of social media, (2) participation in special events, and (3) backing from the Integrated Islamic Schools Network (JSIT). In the Islamic educational institution management context, these efforts demonstrate a comprehensive strategic approach, involving in-depth analysis of internal and external conditions, reinforcing an Islamic values-based curriculum, and collaborating with the community, government, and parents. Supporting factors include strong leadership, social acceptance, and adequate infrastructure, while challenges encompass perceptions of high education costs and social dynamics. This strategy reflects a modern, adaptive, and values-based approach to Islamic education.